Court Decision Contra Legem or an Application of the Principle of Proportionality in Concreto? - Dambrauskaitė, Asta (Teisė, 2021)
The article analyses cases of non-application of a national legal rule by cassation court judges hearing civil cases where, based on the analysis of concrete circumstances, the application of such a rule, in the opinion of judges, would lead to an infringement of the principle of proportionality and the European Convention on Human Rights. Decisions of two courts of cassation belonging to the continental law tradition (the Lithuanian Supreme Court and the French Court of Cassation) illustrate such a control of the application of the principle of proportionality in concreto. While national law is subject to an increasing impact of the case law of supranational courts, the legitimacy of such national court decisions is discussed also in the context of the transformations taking place in regard to the role of a judge.